Isolasi Senyawa Saponin dari Mangrove Tanjang (Bruguiera gymnorrhiza) dan Pemanfaatannya sebagai Pestisida Nabati pada Larva Nyamuk - Alowisya F. Liem; Elisabeth Holle; Ivone Y. Gemnafle; Sarah Wakum (Jurnal Biologi Papua, 2013)
Bruguiera gymnorrhiza is a mangrove plant often called tanjang containing several chemical compounds such as saponins, alkaloids, tannins, flavonoids and polyphenols. The purpose of this study was to isolate and determine the toxicity of the methanol extract of bark, leaves and flowers of B. gymnorrhiza as a plant pesticide. Samples were extracted by maceration and soxhletation methods using methanol as solvent. Maceration and soxhletation were done for 24 h and 6 h, respectively. From distillation of maceration treatment was obtained 20.28% (bark), 15.95% (leaves) and 19.69% (interest). In soxhletation there were concentrations of 27.01%, 29.68% and 16, 46%. The results of the foam test and reagent-Buchard Lieberman (LB) showed that only bark and flowers contain saponins. Toxicity tests on mosquito larvae with flower extract by maceration was more toxic than bark; on the contrary bark extract was more toxic than flower extract by soxhletation. SPSS analysis showed LC50 values for flower extracts was 723.6 ppm and for bark extract was 673.9 ppm. Both bark and flower extracts containing saponins can be categorized as highly toxic (<1000 ppm). Therefore it can be used as a botanical pesticide against mosquito larvae.  Key words: mosquito larvae, mangrove tanjang (B. gymnorrhiza), saponins, pesticide.